Comparative electrochemical degradation of the herbicide tebuthiuron using a flow cell with a boron-doped diamond anode and identifying degradation intermediates - Pereira, Gabriel F.; Silva, Bianca F. [UNESP]; Oliveira, Regina V.; Coledam, Douglas A. C.; Aquino, Jose M.; Rocha-Filho, Romeu C.; Bocchi, Nerilso; Biaggio, Sonia R. (Elsevier B.V., 2017)
The electrochemical degradation of tebuthiuron (TBH; 100 mg L (1)) was carried out under enhanced mass transport conditions (using a flow cell with a BDD anode), while investigating the effect of solution pH, absence and presence of Cl ions in the supporting electrolyte solution (0.1 mol L (1) Na2SO4), and current density (j = 10, 30, 50 mA cm (2)) on the herbicide degradation and resulting oxidation intermediates. The enhanced mass transport conditions led to significantly improved performances, comparatively to previous results obtained with a common electrochemical cell. The solution pH or presence of Cl ions did not affect the TBH removal rate. However, the COD removal rate, despite being independent of pH, was significantly faster in the presence of Cl ions, most probably due to false results caused by organochlorinated intermediates. In the absence of Cl ions in solution, the TBH removal rate increased with j, whereas the COD removal rate was not affected, but significantly increased removal rates were attained in the presence of Cl ions, most probably because of increased formation of organochlorines. As expected, higher values of the general and mineralization current efficiencies as well as lower energy consumptions per unit TOC mass removed (ECTOC) were attained at 10 mA cm (2); in the absence of Cl ions, complete removal of TBH and 80% removal of TOC were attained with ECTOC = 0.2 kW h g (1) (less than 1/10 of those for electrolyses using a conventional electrochemical cell). From the identified intermediates, an initial TBH oxidation pathway like those of coupled processes involving photochemistry is expected. Most carboxylic acid intermediates were removed or being removed by the end of the electrolyses (except tartronic acid, which accumulated). As expected, organochlorinated intermediates were identified in the presence of Cl ions, but were completely removed by the end of the electrolyses. In summary, the electrochemical degradation of TBH in the presence of Cl ions is not advantageous; no significant improvement in the TBH and TOC removal rates, or in the energy expense, is achieved and the formation of organochlorines is a real possibility. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Tebuthiuron electrooxidation; Filter-press reactor; BDD anode; Hydroxylation reactions; Chlorine-mediated oxidation